Ramadan and the quran: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"Ramadan and the Quran" highlights the significance of the month of Ramadan in Islamic tradition, emphasizing its role as a time for fasting, prayer, and reflection. During this month, Muslims believe the Quran was revealed to Prophet Muhammad, making it a period for spiritual growth and increased devotion. The narrative often underscores themes of discipline, compassion, and the importance of connecting with one's faith through the teachings of the Quran, fostering a sense of community and self-improvement.